Influence Learning Model Cooperative Integrated Reading and Composition To Ability Writing Ballads And Poems Romance By Indonesian Language Education Study Program Students UHKBPNP - Vita Riahni Saragih; Junifer Siregar (Jurnal Ilmu Sosial dan Humaniora, 2026)
Learning Cooperative Integrated Reading and Composition is a learning model integrated, building cooperation in groups and develop skills think students. Encourage students to be more active and confident in learning Good in a way physique and mental, in the learning process. Improvement results learn on this model increase understanding students and results Study they as well as can overcome difficulty study. Excellent students can help students who are having difficulties in his group, creating atmosphere inclusive learning. Improvement trust self, involvement in discussion and work group can increase trust self student in write poetry. Urgency study based on from existence Independent learning curriculum which emphasizes learning based literacy in accordance development of the times. Research This aim For know the influence of learning models Cooperative Integrated Reading and Composition to Ability Writing Ballads and Poems Romance by Indonesian Language Education Students of UHKBPNP. Output mandatory expected in the form of journal national accredited Syntax 4